(untitled) (Revista de Crítica Literaria Latinoamericana, 2025)
"Between 1870 and 1890 several women’s magazines from Buenos Aires assiduously began to publish texts from Peruvian writers, influenced largely by the arrival of Juana Manuela Gorriti to that city. These magazines became a platform to promote transnational dialogues among their female contributors, legitimizing the figure of the female American writer in this process. This paper aims to study this circuit of publication, which would extend until the late nineteenth century, when writers like Clorinda Matto de Turner and Carolina Freyre de Jaimes settled in Argentina and developed their own journalistic projects there."